Value and Goal-Oriented Dispositives of the Discourse of Cultural Heritage in the Theory of Political Communication - Anna M. Sosnovskaya (Гуманитарный вектор)
Studies of recent years have shown a weakening of the urban identity of the youth of St. Petersburg, a lack of interest in the preservation of cultural heritage. The purpose of the study is to deconstruct discourses and identify the value-oriented and goal-oriented components of dispositives that allow understanding the drives of communication in social networks and adjusting the policy of urban identity. The article applies the actor-network theory to data reconstructed from the texts of social networks of residents and city defenders about the St. Petersburg cultural architectural heritage, which allowed us to adapt the ANT for a systematic analysis of urban identity politics, taking into account infl uential factors in the modern environment of network communications and related policies. Identity is considered simultaneously as a discursive construction and as an effect of the confi guration of human and non-human actors that respond in social practice to the current transformation of the symbiotic relationship between man and the environment. On the material of the media and social networks regarding the destruction of the building, the content was analyzed using the discursive method and actor-network theory. Three possible levels of use of ANT in the analysis of political communication around cultural heritage are identifi ed and illustrated: 1) material objects stabilize social relations; 2) have real and sensual qualities that contribute to projective identifi cation; 3) ensure the spatiality and integrity of the city. In the course of analyzing the boundaries of network interactions, the psychoanalytic concept of “lack” is actualized as an insoluble contradiction and antagonism of discourses, as a projection of anxiety in texts, with the prevailing uncertainty of the current motivation. The result of the study was the identifi cation of value-oriented and goal-oriented dispositives of discourses in the fi eld of urban identity and the development of a program for the policy of communication with network actors. The identifi cation of dispositives allowed us to establish the conditions for productive communication as a determining factor in symbiotic regimes in the modern city